King in the wilderness [videorecording (DVD)] - Kunhardt, Peter W. (Allied Vaughn., 2018)
Provides a look at the final three years in the life of Martin Luther King, Jr., from the passage of the Voting Rights Act in 1965 to his assassination in April 1968, looking at his character, his commitment to nonviolence and peaceful protest, and his personal philosophical struggles.